The Russian Military Commitment in Syria and the Eastern Mediterranean: Power, Prestige and Popularity. Issue 4 (4th July 2018) - Thornton, Rod
Abstract : Western powers are normally keen to stress that their overseas military interventions will be distinctly finite. Russia's President Vladimir Putin, however, is doing no such thing in relation to Syria. As Rod Thornton shows, he has made it clear that the commitment of Russian forces to the Eastern Mediterranean region is very much for the long haul.